2001 Special Merit Award for Outstanding Achievement in Community Dentistry-International: Dr. Fumio Y amashita - Dushanka V. Kleinman, DDS, MScD (Blackwell Synergy, 2001)
It is a distinct honor that we are able to present the 2001 Special Merit Award for Outstanding Achievement in Community Dentistry-International to Dr. Fumio Yamashita posthumously for his many achievements in preventive dentistry and community efforts. Today we have the pleasure of having Dr. Yamashita’s wife with us to receive the award